'A Leg to Stand On' by Oliver Sacks: a unique autobiographical account of functional paralysis. Issue 9 (7th August 2012) - Stone, Jon; Perthen, Jo; Carson, Alan J
Abstract : Oliver Sacks, the well known neurologist and writer, published his fourth book, 'A Leg to Stand On', in 1984 following an earlier essay 'The Leg' in 1982. The book described his recovery after a fall in a remote region of Norway in which he injured his leg. Following surgery to reattach his quadriceps muscle, he experienced an emotional period in which his leg no longer felt a part of his body, and he struggled to regain his ability to walk. Sacks attributed the experience to a neurologically determined disorder of body-image and bodyego induced by peripheral injury. In the first edition of his book Sacks explicitly rejected the diagnosis of 'hysterical paralysis' as it was then understood, although he approached this diagnosis more closely in subsequent revisions. In this article we propose that, in the light of better understanding of functional neurological symptoms, Sacks' experiences deserve to be reappraised as a unique insight in to a genuinely experienced functional/psychogenic leg paralysis following injury.